If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 3(2x + -9) = 69 Reorder the terms: 15x + 3(-9 + 2x) = 69 15x + (-9 * 3 + 2x * 3) = 69 15x + (-27 + 6x) = 69 Reorder the terms: -27 + 15x + 6x = 69 Combine like terms: 15x + 6x = 21x -27 + 21x = 69 Solving -27 + 21x = 69 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 21x = 69 + 27 Combine like terms: -27 + 27 = 0 0 + 21x = 69 + 27 21x = 69 + 27 Combine like terms: 69 + 27 = 96 21x = 96 Divide each side by '21'. x = 4.571428571 Simplifying x = 4.571428571
| 14Z+17=0 | | 0.1(16+y)+.5y=-3.8 | | 0.4+0.25t=0.2 | | 12y=4x-16 | | Y-21-34Y=3 | | 8y=4x+6 | | 0.2x=3.2+0.2y | | 110=9x-7 | | (2w+3)(3w-6y-7)= | | 14d+4=5d+58 | | -6-5=-41 | | 4(x-6)=3.2 | | 8-5x=37 | | 3(a+3)=14.4 | | 6/x+2/2x=8/x+1/3 | | 3x-2(-10)=5 | | 29.8=6c-5 | | 4(5/3+2/3y)-5y=30 | | 8e-7=31.4 | | y+3=-5/4x-(-5/4)*1 | | -2[7x-7-6(x+7)]=2x+5 | | 3p=16.4 | | 5x+9=41 | | 8x-12=16x | | 3x+7/x-2-x-4/3x-6 | | 8(a+2)=88 | | 11=6c-7 | | 4x+39=13 | | 6(x/2-y/3)=6(5/6) | | 4y-10+y+60=5y+50-3y | | 4y-7=28 | | x/5-y/4=15/10 |